2023
DOI: 10.1002/acn3.51798
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged perivascular spaces in patients with migraine: a case–control study based on 3T MRI

Ziyu Yuan,
Wei Li,
Hefei Tang
et al.

Abstract: Objective To explore whether MRI‐visible enlarged perivascular spaces (EPVS) are associated with migraine and may serve as a predictor of migraine. Then further explore its correlation with migraine chronification. Methods A total of 231 participants (healthy control [HC] = 57, episodic migraine [EM] = 59, chronic migraine [CM] = 115) were included in this case–control study. A 3T MRI device and the validated visual rating scale were used to assess the grades of EPVS in centrum semiovale (CSO), midbrain (MB), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Neuroinflammation, excess of calcitonin gene-related peptide (CGRP) and cortical spreading depression are the three most studied mechanisms underlying migraine pathogenesis and aura development. A common feature of these mechanisms is the impairment of the glymphatic system [ 2 , 5 , 7 23 ].…”
Section: Migraine Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Neuroinflammation, excess of calcitonin gene-related peptide (CGRP) and cortical spreading depression are the three most studied mechanisms underlying migraine pathogenesis and aura development. A common feature of these mechanisms is the impairment of the glymphatic system [ 2 , 5 , 7 23 ].…”
Section: Migraine Diseasementioning
confidence: 99%
“…Within the CSF-ISF, it reaches the perivenous space and hence the bigger dura mater sinus. Then, the final step are the lymph nodes of the general lymphatic system [ 2 ]. It can been postulated that an impairment of the GS may increase CGRP concentration and thus worsen migraine.…”
Section: Glymphatic Dysfunction In Migrainementioning
confidence: 99%
See 1 more Smart Citation
“…However, this study only recruited patients with EM, leaving patients at the worse end of the disease spectrum (ie, CM) unexplored. Another study found enlarged perivascular spaces in patients with migraine, implicating a potential role of glymphatic dysfunction in migraine 19 . However, this speculation has not been verified by the evaluation of glymphatic dynamics.…”
mentioning
confidence: 96%
“…However, this speculation has not been verified by the evaluation of glymphatic dynamics. Moreover, the function of the mLVs in patients with migraine has not been explored 18,19 …”
mentioning
confidence: 99%